Treatment Choices Based on OncotypeDx in the Breast Oncology Care Setting - Malo, Teri L. (Hindawi Publishing Corporation, 2012)
Introduction. This study aimed to evaluate whether OncotypeDx test results predict receipt of adjuvant chemotherapy in breast cancer patients who received an OncotypeDx recurrence score (RS). Materials and Methods. Pathology records were used to identify breast cancer patients who had OncotypeDx testing between December 2004 and January 2009 (n = 118). Patient sociodemographic information, tumor characteristics, RS, and treatment-specific data were collected via chart review. RS was classified as follows: low (RS ≤ 17), intermediate (RS = 18–30), or high (RS ≥ 31). Bivariate analyses were conducted to investigate the relationship between adjuvant chemotherapy receipt and each sociodemographic and clinical characteristic; significant sociodemographic and clinical variables were included in a multivariable logistic regression model. Results. In multivariable analysis controlling for tumor size, histologic grade, and nuclear grade, only RS remained significantly associated with chemotherapy uptake. Relative to low RS, an intermediate (adjusted odds ratio [AOR], 21.24; 95% confidence interval [CI], 3.62–237.52) or high (AOR, 15.07; 95% CI, 1.28–288.21) RS was associated with a greater odds of chemotherapy uptake. Discussion. Results indicate that RS was significantly associated with adjuvant chemotherapy uptake, suggesting that OncotypeDx results were used to inform treatment decision making, although it is unclear if and how the information was conveyed to patients.